2018
DOI: 10.2147/copd.s153326
|View full text |Cite
|
Sign up to set email alerts
|

Critical regulation of inflammation via class A scavenger receptor

Abstract: BackgroundInflammation is an important cause of COPD. Alveolar macrophages are the major innate immune cells that have an important role in COPD pathology. Class A scavenger receptor (SR-A) is a pattern recognition receptor expressed on macrophages. This study investigates the role of SR-A in COPD progression via regulation of inflammation.Patients and methodsSR-A expression in COPD patients and control subjects (smokers and nonsmokers without COPD) was measured by immunohistochemistry, immunofluorescence, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that SR class A is not only involved in the recognition and clearance of modified lipids (such as oxLDL) but also participates in the regulation of inflammation in several diseases, such as atherosclerosis and chronic obstructive pulmonary disease. 11 , 12 To evaluate the association between SR‐A + monocytes and vulnerable plaques, Emura et al established an SR‐A index, in which the upper normal limit of SR‐A + monocytes in 10 high‐power fields of peripheral blood smear samples was 30 cells. The researchers revealed that a high SR‐A index (> or =30) was associated with an indication of disrupted, fissured, or eroded plaques in patients with acute coronary syndrome (ACS).…”
Section: Association Between Each Sr and ...mentioning
confidence: 99%
“…Previous studies have suggested that SR class A is not only involved in the recognition and clearance of modified lipids (such as oxLDL) but also participates in the regulation of inflammation in several diseases, such as atherosclerosis and chronic obstructive pulmonary disease. 11 , 12 To evaluate the association between SR‐A + monocytes and vulnerable plaques, Emura et al established an SR‐A index, in which the upper normal limit of SR‐A + monocytes in 10 high‐power fields of peripheral blood smear samples was 30 cells. The researchers revealed that a high SR‐A index (> or =30) was associated with an indication of disrupted, fissured, or eroded plaques in patients with acute coronary syndrome (ACS).…”
Section: Association Between Each Sr and ...mentioning
confidence: 99%
“…Gut microbiota grows mainly based on dietary nutrients, and its metabolites, which in turn modulate host mucosal immunity through downstream mechanisms, including stimulation of regulatory T-cells and cause pro-inflammatory signals [166]. LPS, a major cell wall component of Gram-negative bacteria, is known to be potent endotoxin in inducing chronic inflammation [167]. When binding to CD14 and Toll-like receptor4 (TLR4) on the surface of macrophage, a high concentration of LPS can initiate a downstream series of inflammatory mechanisms [35,168].…”
Section: Role Of Gut Microbiota In Diabetesmentioning
confidence: 99%
“…Class A scavenger receptors (SR-A) are mainly expressed in macrophages. SR-A could increase inflammation, [ 42 ] and COPD is associated with SR-A gene sequence variation [ 43 ]. However, Crbn KO did not change the levels of SR-As as in SR-A1 or the macrophage receptor with the collagenous structure (MARCO) in LPS- or elastase-treated BMDMs ( Supplementary Figures S3 and S4 ).…”
Section: Discussionmentioning
confidence: 99%